Research on the compatibility of the calculation methods of rolling‐stock brakes - Bureika, Gintautas; Mikaliūnas, Šarūnas (Transport, 2008)
One of the main tasks approached by the European Union is the liberalisation of railway transport service market. The foremost problem solved in this paper is the interoperability of various railway systems in the countries of the European Union. Thus, the immediate goal is to solve the problem of the interoperability of different railway systems used in the European Union. A distinction between railway track gauges (from 1435 to 1668 mm), particular couples of wagons, various clearances of rolling stock, different systems of infrastructure etc. are the main impediments. One of the problems in the nearest future will be the evaluation of the brakes of different wagons produced in Western Europe and the former Soviet Union. Freight trains in Lithuania consist of these two types of wagons, and therefore some problems of correcting the results of calculating braking distances and brake force may arise. The main object of this research is to investigate the methods evaluating the brakes of rolling‐stock and to assess the possibilities of integrating and harmonizing these different methods. The reliability of the methods evaluating the brakes of rolling‐stock is one of the most important components enabling the interoperability of railway transport in the EU network. The brakes of Russian wagons are calculated by MPS Rules for Traction Calculations, approved by the Russian Ministry of Transport (till 2004 ‐ Ministry of Communication Ways of Russia)). On the other hand, the brakes of the wagons produced in Western Europe should be calculated applying TSI (Technical Specifications for Interoperability) methodology. The main parameter following TSI (Technical Specifications for Interoperability) methodology is braked mass and following MPS (Railway Transport Ministry of Russia) method ‐ a pressing force of the brake shoes. The questions of determining the braked mass of wagons and correcting mean braking distance are presented. The compatibility of two different evaluating methods is discussed. Finally, the basic conclusions are given. First published online: 27 Oct 2010